2009
DOI: 10.1621/nrs.07001
|View full text |Cite
|
Sign up to set email alerts
|

The steroid and xenobiotic receptor (SXR), beyond xenobiotic metabolism

Abstract: The steroid and xenobiotic receptor (SXR) (also known as pregnane X receptor or PXR) is a nuclear hormone receptor activated by a diverse array of endogenous hormones, dietary steroids, pharmaceutical agents, and xenobiotic compounds. SXR has an enlarged, flexible, hydrophobic ligand binding domain (LBD) which is remarkably divergent across mammalian species and SXR exhibits considerable differences in its pharmacology among mammals.The broad response profile of SXR has led to the development of "the steroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
185
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(193 citation statements)
references
References 207 publications
7
185
0
1
Order By: Relevance
“…We and other groups have shown that activation of PXR also affects the expression of other hepatic genes involved in lipid homeostasis, including apoA-IV, oxysterol 7 ␣ -hydroxylase (CYP39A1), and 7-dehydrocholesterol reductase (DHCR7) in several animal models including WT, apoE ( 9,19,20 ). These studies indicate that PXR can mediate cholesterol and lipid homeostasis at multiple levels.…”
Section: Rna Isolation and Quantitative Real-time Pcr Analysismentioning
confidence: 76%
“…We and other groups have shown that activation of PXR also affects the expression of other hepatic genes involved in lipid homeostasis, including apoA-IV, oxysterol 7 ␣ -hydroxylase (CYP39A1), and 7-dehydrocholesterol reductase (DHCR7) in several animal models including WT, apoE ( 9,19,20 ). These studies indicate that PXR can mediate cholesterol and lipid homeostasis at multiple levels.…”
Section: Rna Isolation and Quantitative Real-time Pcr Analysismentioning
confidence: 76%
“…Novel physiological functions of PXR have been discovered including regulation of NF-kB-mediated inflammatory pathway, vitamin D metabolism, cholesterol and lipid homoeostasis, energy homoeostasis, apoptosis as well as cell proliferation (reviewed in Zhou et al, 2009). These new results suggest multitudes of PXR functions and potential use of PXR as a therapeutic target for treating certain diseases such as inflammatory bowl disease (IBD), cholestasis and hyperlipidemia in which PXR may influence the disease development.…”
mentioning
confidence: 99%
“…In 1998, SXR/PXR was cloned as a novel nuclear receptor that is mainly expressed in the liver and intestine [6]. At first, its functions were characterized as a ligand-dependent transcription factor which is activated by various pharmaceutical agents and xenobiotic compounds [7]. It was originally classified as an orphan receptor since the endogenous ligand was not known when it was cloned.…”
Section: Multiple Mechanisms Of Vitamin K Functionmentioning
confidence: 99%